Examining the Impact of Interdisciplinary Practices on Secondary School Students' Awareness of Sustainable Living - YÜZBAŞIOĞLU, Mustafa Kemal (Kastamonu Egitim Dergisi, 2023)
Purpose: This study aimed to determine the effect of the practices carried out according to an interdisciplinary approach on students' awareness of sustainable living.
Methodology: In the present study, one group pre-test post-test experimental design, one of the quasi-experimental methods, was used. A total of 46 activities were carried out in 33 weeks of the academic year within the scope of 11 different courses and social club practices with 37 secondary school students who participated in the study. The study data were collected using the Sustainable Living Awareness Scale.
Findings: As a result of the activities carried out, students' awareness of sustainable living increased significantly on an overall scale and in the social, economic, and environmental sub-dimensions of the scale.
Highlights: The present study concluded that the activities carried out over a long period with an interdisciplinary approach reflected positively on the awareness of the students. It is recommended to take steps to make teacher candidates and teachers aware of the concept of sustainable development and for the development of teacher candidates and teachers on sustainable development.
Keywords: 4. Education; 12. Responsible consumption